Hegemonia discursiva e campo escolar: a percepção de professores sobre a militarização de escolas públicas no Estado do Paraná - Mingori, Rodrigo Luis (2023)
The present study was part of the research line: Society, Knowledge, and Education and aimed to analyze the historical, social, and political process of institutionalizing the militarization policy of public education in the Brazilian context, through the Civic-Military Schools Programs, their developments in the state of Paraná, and particularly within a public school in the municipality of Francisco Beltrão using the discourse theory produced by the Argentine Ernesto Laclau and Chantal Mouffe. Our study was supported by the post-structuralist methodological assumption of discourse analysis and involved field research in the Focus Group mode with the teachers of a militarized institution. By analyzing the adherence and perception of teachers from a militarized public institution in the state of Paraná, it was possible to perceive the encouragement/endorsement given to the Civic-Military Schools Program by them, a subject position that relates to and acts as evidence of the contemporary neoconservative advance in the regions of the global south in the face of right-wing and extreme right-wing governments established in the last decade. Thus, it was possible to perceive the relationships that authorize the military body to influence education by dividing the educational field in acting on the discipline of bodies and behaviors in school.